Can Judges Ignore Justifying and Forgiveness Reasons for Justice and Human Rights? - Oksidelfa Yanto Yanto; Imam Fitri Rahmadi; Nani Widya Sari (Faculty of Law, Sriwijaya University, Indonesia, 2022)
In the criminal law system in Indonesia, there are two reasons why an individual suspected of having committed a crime must be released. These two reasons are justifying and forgiveness reasons. In practice, these two reasons are linked to the elimination of criminal acts based on legal justice and human rights. This article discusses the legal consequences when the judge rejects the justifying and forgiveness reasons that can eliminate the sentence. The method used in this research is normative juridical by analysing norms, principles and rules of law with a case approach. As a result, this research shows that judges in practice have the authority given by law to determine whether an action can be categorised as justifying and forgiveness reasons that eliminate punishment by referring to the principles and legal regulations for justice and human rights. However, when the judge ignores these two reasons due to considerations of lack of justice and respect for human rights, this practice can be carried out by the judge with the consequence that this decision will cause harm, suffering and misery for the accused. This article argues that to protect the public interest from wrong decisions is necessary to reform the Criminal Procedure Code (KUHAP) to provide objectivity, honesty, and justice that rely on legal principles and rules.